Treatment of high-energy pilon fractures using the ILIZAROV treatment - Osman, Walid (Pan Afr Med J, 2017)
The management of high-energy pilon fractures is still controversial. Open reduction and internal fixation are often associated with serious complications. Various methods have been used to treat these injuries, with variable results. The aim of this retrospective study was to analyze the clinical and radiographic outcome of the ILIZAROV technique in patients with high-energy pilon fractures. Thirty cases of distal tibia epiphysis fractures (pilon fractures) were managed from 1999 to 2012. The study group included 5 cases of open fractures. The mean age was 47 years. According to Rüedi and Algower classification; 11 fractures were type II, and 19 type III. All fractures were a consequence of high-energy trauma. Fractures of the lower fibula were present in 28 of the patients. An external Fixator was applied for open fractures. Closed injuries were operated on 3 to 13 days after injury, with an average of 8 days. The mean follow-up was 48 months. All fractures united. The external fixator was removed after a mean of 22 weeks (10 - 28 weeks). Two patients with a type III fracture had a delayed union and were treated with corticotomy and dynamisation of the ILIZAROV fixator. Only one secondary displacement of a type III fracture was noted after two months and was treated by adjuction of 2 olive wires. There were no cases of osteomyelitis or deep infections. Pin-tract infections occurred in ten patients. We had not any case of nervous injury due to introduction of the pins. Using radiological criteria for assessement of reduction of the articular fragments, there was excellent and good restoration of articular structure in 24 cases. The average American Orthopeadic Foot and Ankle Society ankle-hind foot score was excellent in 16, good in 6, fair in 6 and poor in 2. Soft tissue healing occurred without need for plastic surgery in all cases. The movements of the ankle ranged from 0 to 20° of dorsiflexion and 5° to 40° of plantar flexion. Twenty patients had gone back to their preinjury profession. The ILIZAROV technique is a safe and a very effective treatment for severe pilon fractures with minimum complications and good healing results.